Functionalization of Fluorinated Benzenesulfonamides and Their Inhibitory Properties toward Carbonic Anhydrases. Issue 4 (10th March 2015) - Dudutienė, Virginija; Zubrienė, Asta; Smirnov, Alexey; Timm, David D.; Smirnovienė, Joana; Kazokaitė, Justina; Michailovienė, Vilma; Zakšauskas, Audrius; Manakova, Elena; Gražulis, Saulius; Matulis, Daumantas
Abstract: Substituted tri‐ and tetrafluorobenzenesulfonamides were designed, synthesized, and evaluated as high‐affinity and isoform‐selective carbonic anhydrase (CA) inhibitors. Their binding affinities for recombinant human CA I, II, VA, VI, VII, XII, and XIII catalytic domains were determined by fluorescent thermal shift assay, isothermal titration calorimetry, and a stopped‐flow CO2 hydration assay. Variation of the substituents at the 2‐, 3‐, and 4‐positions yielded compounds with a broad range of binding affinities and isoform selectivities. Several 2, 4‐substituted‐3, 5, 6‐trifluorobenzenesulfonamides were effective CA XIII inhibitors with high selectivity over off‐target CA I and CA II. 3, 4‐Disubstituted‐2, 5, 6‐trifluorobenzenesulfonamides bound CAs with higher affinity than 2, 4‐disubstituted‐3, 5, 6‐trifluorobenzenesulfonamides. Many such fluorinated benzenesulfonamides were found to be nanomolar inhibitors of CA II, CA VII, tumor‐associated CA IX and CA XII, and CA XIII. X‐ray crystal structures of inhibitors bound in the active sites of several CA isoforms provide structure–activity relationship information for inhibitor binding affinities and selectivity. Abstract : Nanomolar CA binders: We synthesized 64 rationally designed substituted fluorobenzenesulfonamides. Variation of substituents at the 2‐, 3‐, and 4‐positions yielded compounds with a wide range of binding affinities and isoform selectivities. Most 2, 4‐disubstituted‐3, 5, 6‐trifluorobenzenesulfonamides were found to be effective carbonic anhydrase (CA) XIII inhibitors with high selectivity against off‐target CA I and CA II.